Assessment of the Emission and Circumnavigation Pollution of Sulfur Oxide, Nitrogen Oxide, and Total Petroleum Hydrocarbons in the North of Thi-Qar Province, Al Rifaee City, Iraq During 2015-2018 and 2023. - Al Rukabie, Jamal S. Abd (Iraqi Journal of Science, 2025)
Air pollution caused by gas emission dispersion leads to damage of the environment and is harmful to humans. In this article, we study and analyze the gas emissions of nitrogen oxide (NOX), sulfur oxide (SOX), and Total Petroleum Hydrocarbons (TPHs) in Al Rifaee City. The feedback and main source of pollution was due to the production of crude oil from the Gharraf oil field (GOF), located in the northwest direction of Al Rifaee City. The highest monthly total emission rate for all years was for TPHs (79499.8685 MMSCF); it was 6483.69, and 1560.73 tons) for NOX and SOX, respectively. The value of correlation factor R2 for NOX was equal to 0.190, which is higher than SOX and TPHs. In the second part of this article, the concentrations of the above pollutants were measured in the laboratory in September 2023, and the maximum value was for TPHs 610 µg/kg in the soil sample of the northwestern area of Al-Rifaee city center due to crude oil production from the Gharraf oil field (GOF).